Analisis Keefektifan Website Wordwall dalam Meningkatkan Keterlibatan Siswa Kelas 5 pada SDN 1046607 Sei Rotan - Maria Ulfa; Maya Sari Hasibuan; Ahmad Taufik Alafkari Siahaan (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
The decline in student interest in learning in case studies among 5 students at SDN 104607 Sei Rotan has become a significant challenge at SDN 104607 Sei Rotan. This research aims to evaluate the effectiveness of using Wordwall-based learning media in increasing interest in learning PAI among students. The research method used is quasi-experimental research with a pre-test and post-test design in two groups, namely the control group and the experimental group. Data was collected through a learning interest questionnaire and analyzed using the t- test to measure significant differences between the control and experimental groups. The research results show that the use of Wordwall-based learning media significantly improves case studies for 5 students compared to conventional methods.